Analysis of Implementation the Good Nazir Governance (GNG) Index in Waqf Institutions (UIN Sunan Kudus, 2024)
This study investigates the implementation of Good Nazir Governance (GNG) in Indonesian Waqf Institutions, utilizing the GNG Index as an assessment tool. Despite the considerable potential of waqf in Indonesia, governance practices remain relatively underdeveloped. While the GNG Index presents a novel instrument for evaluating waqf performance, prior research on its application has been limited. This research aims to fill this gap by examining the extent to which waqf institutions adhere to GNG principles. Employing a mixed methods approach, combining qualitative and quantitative data collected through purposive sampling and a questionnaire, this study reveals that only 45 percent of the 20 sampled waqf institutions achieve a